1981
DOI: 10.1084/jem.154.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Binding of bacillus Calmette-Guérin-activated macrophages to tumor targets. Selective inhibition by membrane preparations from homologous and heterologous neoplastic cells.

Abstract: The binding of tumor cells by activated macrophages is an initial and necessary event in the cytolysis of these targets. The data here indicate that membrane preparations from RL sigma 1 leukemia targets, EL-4 lymphoma targets, and P815 mastocytoma targets each inhibited binding of its homologous target to bacillus Calmette-Guérin (BCG)-activated murine macrophages in a dose-dependent fashion. Similar amounts of membrane from lymphocytes did not alter binding of the three neoplastic target to BCG-macrophages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For example, gangliosides have been shown to function as receptors for molecules with immunomodulatory activites such as interferon (Besancon et al, 1976;Vengris et al, 1976) and migration inhibition factor (Higgins et al, 1978). It has also been reported that Ia or closely related molecules have carbohydrates as antigenic determinants (McKenzie et al, 1977;Parish et al, 1978) and have the ability to bind various mono-or oligosaccharides (Mann and . Furthermore, mono-and oligosaccharides have been shown to inhibit a wide range of immunologic reactions including murine and human natural cytotoxicity (Stutman et al, 1980a, b;Wright and Bonavida, 1981;Forbes et al, 1981), human monocyte killing of red blood cells (Muchmore et af., 1981), activation of cytotoxic murine macrophages (Thomasson and Stewart, 1980), T-cell suppressor activity (Koszinowski and Kramer, 1981) and secondary IgG antibody responses (Tomaska and Parish, 1981).…”
mentioning
confidence: 99%
“…For example, gangliosides have been shown to function as receptors for molecules with immunomodulatory activites such as interferon (Besancon et al, 1976;Vengris et al, 1976) and migration inhibition factor (Higgins et al, 1978). It has also been reported that Ia or closely related molecules have carbohydrates as antigenic determinants (McKenzie et al, 1977;Parish et al, 1978) and have the ability to bind various mono-or oligosaccharides (Mann and . Furthermore, mono-and oligosaccharides have been shown to inhibit a wide range of immunologic reactions including murine and human natural cytotoxicity (Stutman et al, 1980a, b;Wright and Bonavida, 1981;Forbes et al, 1981), human monocyte killing of red blood cells (Muchmore et af., 1981), activation of cytotoxic murine macrophages (Thomasson and Stewart, 1980), T-cell suppressor activity (Koszinowski and Kramer, 1981) and secondary IgG antibody responses (Tomaska and Parish, 1981).…”
mentioning
confidence: 99%
“…Although cell-surface molecules have been thought to be involved, the molecular components important in effector-cell-tumor-cell binding have not been identified. Either intact tumor cells or membrane fragments of tumor cells have been shown to inhibit the binding of neoplastic targets to isolated peritoneal MOs (Marino and Adams, 1980b;Marino et al, 1981). This supports the concept that the initial effector-target recognition may be mediated via specific cell membrane receptor molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Weir et al (1979) have suggested that macrophages may in fact adhere to tumor cells by lectin-like MO cell surface receptors. Since activated MOs have been shown to adsorb the capacity of tumor cell membranes to inhibit MO-tumor-cell binding (Marino et al, 1981), it may be that membrane structures expressed on the tumor cell may interact with specific receptor molecules on the MO in order to allow effective MO-tumor-cell conjugate formation. This is consistent with observations by electron microscopy of distinct regions of attachment between the membranes of MOs and bound tumor cells (Muse and Koren, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…At present we do not know the mechanism(s) for the M#-resistance of the variants selected in vivo and in vitro. Mq~-mediated target cytolysis probably involves several independent functions including binding to a target structure on the neoplastic cells (21) and subsequent mediation of cytolysis (22). The binding of M~ to certain target structures present within the plasma membranes of the tumor cells is known to be an initial and…”
Section: Discussionmentioning
confidence: 99%
“…Vertical bars represent the SEM fur the individual analysis of the number of mice indicated above. necessary event in the cytolysis of these targets (21). A recent study comparing a variety of other, different tumors indicated that M4~ may still bind to a large number of target ceils that are insensitive to lysis (23).…”
Section: Deys After Tumor Chollengementioning
confidence: 99%